Remnant cholesterol and risk of aortic aneurysm and dissection: a prospective cohort Study from the UK biobank study and mendelian randomization analysis - Ting Zhou; Wenhui Lin; Bangyuan Yang; Yuan Liu; Wenhui Huang; Nianjin Xie; Fan Yang; Zhuoheng Lin; Ziyang Hu; Songyuan Luo; Jianfang Luo (Lipids in Health and Disease)
Abstract Aim This study aimed to examine the relationships between remnant cholesterol (RC) and the risk of aortic aneurysm and dissection (AAD). Methods This prospective cohort study included 368,139 European adults from the UK Biobank. Additionally, the causal relationship between RC and AAD was investigated using Mendelian randomization (MR) analyses. Results During a median follow-up of 13.65 years, 1,634 cases of abdominal aortic aneurysm (AAA), 698 cases of thoracic aortic aneurysm (TAA), and 184 cases of aortic dissection (AD) were identified. Elevated RC levels were associated with an increased risk of AAA compared to the reference group ([highest vs. lowest RC levels]: adjusted hazard ratio (HR) = 1.65, 95% CI: 1.36–1.99). However, no significant association was observed between high RC levels and the risk of either TAA or AD. Two-sample MR analyses supported a significant causal effect of RC on AAA risk (odds ratio (OR) = 2.08, 95% CI: 1.70–2.56). The association between RC and AAA persisted after adjusting for the effects of RC-associated genetic variants on low-density lipoprotein cholesterol (LDL-C). In contrast, MR analyses did not indicate any causal associations between RC and TAA or AD. Conclusions Elevated RC was linked to a greater risk of developing AAA, with MR analyses confirming a causal relationship. These findings suggest that RC may function as a new biomarker for AAA and could be integral to strategies aimed at preventing AAA.